CYCAS RUMPHII MIQ. DI SEPANJANG SUNGAI MANINGO, TAMAN WISATA ALAM CANI SIRENRENG - Mudiana, Deden (Bumi Lestari, 2009)
Cycas rumphii Miq. belongs to Cycadaceae family that one of ancient species on the world. Sulawesi is one of distribution area for this species. This research aims to do inventory, habitat and distribution study of Cycas rumphii along Maningo river in Cani Sirenreng Forest Park.Collected data were diameter breast height, height of trunk, altitude, geografphic position (with GPS), and number of individu. Thirty two individuals were recorded on location. Most of them grew in shading area, clay and sandy soil, at 386-417 meter from above sea level.
Keywords: Cycas rumphii; forest park; river; habitat; species